Affective Participation From the In-Between: The Platformization of K-Pop Fandom - Samantha James (Social Media + Society)
As K-pop fans around the world participate in their fan communities in hybrid online-offline contexts, their sense of connection with artists and one another is shaped by their unique position in-between co-creators and resistors within the platform ecosystem. This article draws upon 10 months of fieldwork from 2022 to 2023 to offer a framework for how fans navigate platformization and offers a theoretical contribution to platform studies by advancing the theory of affective participation from the in-between. As a process, platformization involves the shifting of everyday experiences from offline interaction to technologically mediated interaction. For K-pop fans, platform infrastructures change participation in the realm of quantification and identification. This project delves into the relationship between K-pop fans and power structures within this contemporary capitalist system. I argue that, although fans work to creatively subvert systems of power within platformization, through navigation practices such as gatekeeping insider knowledge, community policing, and self-cooptation, they reinvent community structuring systems that serve to benefit K-pop industry leaders and platform owners. However, their creative platform use illuminates a potential for affective participation in the in-between —simultaneously subverting and supporting industry expectations. Fans’ unique relationship with industry leaders and one another demonstrate the contradictory textured affective sensations which allow them to participate in fandom in unique ways. By offering this textured approach to affective participation, this article provides meaningful footing for future research on contemporary participation in global platformized contexts.